Will Affirmative Action Policies Eliminate Negative Stereotypes - Coate, Stephen; Loury, Glenn C. (American Economic Review, 1992)
A key question concerning affirmative action is whether the labor-market gains it brings to minorities can continue without it becoming a permanent fixture in the labor market. The authors argue that this depends on how the policy affects employers' beliefs about the productivity of minority workers. They study the joint determination of employer beliefs and worker productivity in a model of statistical discrimination in job assignments. The authors prove that, even when identifiable groups are equally endowed ex ante, affirmative action can bring about a situation in which employers (correctly) perceive the groups to be unequally productive, ex post. Copyright 1993 by American Economic Association.